Vietnamese Parents’ Attitudes Towards Western-based Behavioral Parent Training - Nam, Trần Thành; Weiss, Bahr (VNU Journal of Science: Education Research, 2015)
Behavioral Parent Training (BPT) interventions have been found effective in reducing a wide range of child behavior problems. However, most relevant research has been conducted in Western countries that may differ along significant cultural dimensions from Asian countries. Thus, the relevance and utility of Western-based BPT for Asian’s population like Vietnam is unclear.  The present study assessed parents’ beliefs about the acceptability, perceived feasibility, and anticipated effectiveness of Western BPT techniques in Vietnam. A sample of 303 Vietnamese parents with a child enrolled in the fourth or fifth grade participated in the study. Vietnamese parents reported using significantly more BPT-congruent than BPT-noncongruent responses toward less serious child misbehaviors (e.g., arguing) but significantly more BPT-noncongruent than BPT-congruent responses towards more serious misbehavior (e.g., fighting). Parents reported relatively little use of harsh responses (e.g., tying their child up in a chair) although their use was significantly greater than “never”. Vietnamese parents were significantly most like to seek help from school personnel (a teacher or school principal) and were significantly least likely to seek help for child behavior problems from a psychologist. Overall, the results suggest that Vietnamese parents are open to trying BPT techniques to help with child behavior problems. The higher parent’s Income, Education and Western acculturation level are, the more tendency Vietnamese parents have positive attitudes towards BPT techniques. Keywords: Behavioral Parent Training, Acceptability, Vietnam.